Gluten Related Disorders Coeliac Disease and Beyond - Comino, Isabel; Sousa, Carolina (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Among gluten-related disorders, coeliac disease (CD) is the best-known one to date, a chronic immune-mediated enteropathy triggered by exposure to gluten in genetically predisposed individuals. It is a common disease, occurring at all ages and characterized by a wide spectrum of clinical manifestations, affecting any organ or tissue. The diagnosis rate of this pathology has increased in the last 10 years, so worldwide epidemiologic data are now available that show that CD is ubiquitous, with a prevalence of 1.4%, higher in female than male individuals. Currently, the only effective treatment for CD is strict and lifelong adherence to a gluten-free diet (GFD). However, CD research is changing rapidly due to the continuous advancing of knowledge. For this reason, the main goal of this Special Issue has been to address the existing knowledge gaps and help advance such important aspects as the pathophysiology, diagnosis, follow-up, and therapeutic options of this pathology. This Special Issue includes 12 peer-reviewed articles reporting on the latest research findings in and evidence related to CD. The published articles cover a range of topics central to CD and GFDs.